A Study on productivity performance of Small and Medium Enterprise (SMEs) in Malaysia / Siti Amierah Ismail - Ismail, Siti Amierah (2011)
The purpose of this study is to determine the relationship between number of employees, salaries & wages paid and export goods with productivity performance on manufacturing production within 96 months starting from the year 2003 to 2010. The scope of this study is focusing on the factors that give the effect to the productivity performance of SMEs in manufacturing production. SME’s in Malaysia existed a long time ago but it was established and encouraged by the government in 1996. The data collection was based on monthly basis, apart from that, secondary data were also used. The methods use to measure the objective of the study are multiple linear regression. From the result, all independent variable which are number of employees, salaries & wages paid and export goods have significant relationships with the productivity performance on manufacturing production. Thus all variables are the most effective variable for the productivity performance on manufacturing production. Since the researcher had identified the most effective variables, it is recommended for company to take all variables as a consideration when making decisions regarding to the productivity performance of Small and Medium Enterprise (SMEs) in Malaysia